1999
DOI: 10.1785/gssrl.70.5.577
|View full text |Cite
|
Sign up to set email alerts
|

An Automatic Method for Determination of Lg Arrival Times Using Wavelet Transforms

Abstract: The regional phase Lg is often used to estimate location and magnitude for sources closer than 1500 km.The complexity of Lg waveforms makes it difficult to consistently determine a unique Lg arrival time, thus affecting source location with a single station or array. This study tests an automatic method for timing Lg arrivals using wavelet transforms to decompose the Lg signal into its components localized both in time and scale.A Continuous Wavelet Transform (CWT) using a Daubechies order two (db2) wavelet is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Anant & Dowla (1997) compared polarization information across a number of scales in determining P ‐phase arrival time, and used transverse compared to radial amplitude information at different scales in determining S ‐phase. Similar research was done by Tibuleac & Herrin (1999) in a study of Lg ‐phase arrivals using wavelets. Lilly & Park (1995) used multiwavelets to estimate the time‐varying spectral density matrix for three‐component seismic data.…”
Section: Introductionsupporting
confidence: 54%
“…Anant & Dowla (1997) compared polarization information across a number of scales in determining P ‐phase arrival time, and used transverse compared to radial amplitude information at different scales in determining S ‐phase. Similar research was done by Tibuleac & Herrin (1999) in a study of Lg ‐phase arrivals using wavelets. Lilly & Park (1995) used multiwavelets to estimate the time‐varying spectral density matrix for three‐component seismic data.…”
Section: Introductionsupporting
confidence: 54%
“…Applications of wavelets have been made for several aspects of seismic signal processing such as the determination of an onset time of specific phase's arrival [2,73], measurement of an anisotropy rate in certain regions [5], and estimation of a time varying spectral density matrix [52]. However, the applications of wavelets are not restricted to signal processing and have been extended to numerical analysis as well exploiting the adaptivity, compactness achievable in the wavelet domain.…”
Section: Previous Wavelet-based Techniques and Motivation Of This Studymentioning
confidence: 99%
“…In their study, Tibuleac and Herrin (1999) also showed that, in the same frequency range, the amplitude difference between the Lg signal and the coda before Lg is much less after Fourier prefiltering than after wavelet prefiltering.…”
Section: Thresholdmentioning
confidence: 92%
“…Different types of seismic phase-pickers, in time or frequency domain, have been previously developed (see Tibuleac and Herrin, 1999). Most of these techniques were developed to pick first arrivals, and none was demonstrated to be optimal for picking secondary phases.…”
Section: Introductionmentioning
confidence: 99%